Dialog Antara Agama: Realiti dan Prospek di Malaysia Religious Dialogue: Its Reality and Prospects in Malaysia - Rahimin Affandi Abd. Rahim,; Mohd Anuar Ramli,; Paizah Ismail ,; Nor Hayati Mohd Dahlal, (Kajian Malaysia, 2011)
Religious dialogue has become an effective mechanism in promoting ethnic and religious harmony. After declaring 2001 as the year of dialogue among civilisations, this approach has been well received in Malaysia. As a result, several dialogues of civilisation and religions had taken place. Although these dialogues were lifeless and cautious in the beginning, they began to develop in a positive manner forging understanding and at the same time minimising conflicts. This article essentially discusses religious relations in Malaysia that are marked by several major and minor conflicts, with the offer of a dialogue mechanism for religious groups as an alternative solution. In this proposed dialogue, certain code of ethics needs to be adhered to by all parties concerned so that its benefits can be attained within the Malaysian reality. Dialog agama merupakan mekanisme berkesan dalam mewujudkan perpaduan kaum dan agama. Selepas diisytiharkan tahun 2001 sebagai tahun dialog, pendekatan ini mula diterima ramai. Kesannya, lahir beberapa siri dialog antara peradaban dan agama. Walaupun pada mulanya bersifat kaku dan berhati-hati, kini ia berkembang ke arah lebih positif dalam mewujudkan persefahaman dan pada masa yang sama meminimumkan konflik. Artikel ini pada dasarnya akan membincangkan tentang senario hubungan agama di Malaysia yang diwarnai dengan konflik yang besar mahupun kecil, dengan penawaran mekanisme dialog antara agama sebagai alternatif penyelesaian. Dalam dialog ini, ada etika yang perlu diamalkan oleh semua pihak yang terlibat agar ia dapat dijayakan dengan berkesan dalam realiti Malaysia.